Justice and prudence in the polis: some reflexions on the digression of the Theaetetus - Borges, Anderson de Paula (Revista Archai, 2010)
My purpose in this essay is to make some remarks about the Digression of the Theaetetus. I shall argue that one central aim of the Digression is to show that there is a conflict between two ways of life: the life of the philosopher and the life of people get involved in politics. In the first part of this paper I make some considerations on the relationship between the Prologue and the trial of Socrates. In the second part I examine the moral of the Digression from the perspective of Socrates”Ÿ account of Protagoras”Ÿ epistemology.